Religiosity among older muslim Malaysians : gender perspective. - Momtaz, Yadollah Abolfathi; Tengku Abdul Hamid, Tengku Aizan; Yahaya, Nurizan; Ibrahim, Rahimah (Taylor & Francis, 2010)
Gender differences in religiosity have been studied in non-Islamic countries and it has been noted consistently that women tend to be more religious than men. However, the role of gender in relation to religiosity is not clear among adherents of the Islamic faith. This study aimed to explore gender differences in religiosity among 1,415 (n = 722 women; n = 693 men) Muslim Malaysians aged 60 years and older. Data for this study came from a national survey, Patterns of Social Relationship and Psychological Well-Being Among Older Persons in Peninsular Malaysia (PSRPWO), which was conducted in peninsular Malaysia during 2007–2008. Religiosity was measured using 11 items from the Intrinsic/Extrinsic Religiosity Scale-Revised. In this study, the reliability test of the scale was established with Cronbach's alphas of 0.85. The Statistical Package for the Social Sciences (SPSS Version 13) was used in data analysis and was performed in two stages. First, gender differences in religiosity were assessed using t-test and bivariate correlations. In the second stage, a hierarchical regression analysis was utilized to examine gender differences in religiosity by controlling for household income, location of residence, marital status, and age. Independent t-test and bivariate correlations showed a significant mean difference in which older men were more religious than older women. In addition, the results of hierarchical regression analyses revealed that gender was a significant predictor of religiosity. The findings of this study indicated that older men displayed significantly higher levels of religiosity than did older women, after controlling for household income, location of residence, marital status, and age.